Improving Buffalo City's sub-transmission reliability - Bentil, Joseph Kingsley Attom (Department of Electrical Engineering, 2017)
Several experiences of sudden large scale disruptions in electrical service deeply impacted both social stability and economic development in affected communities and caused lower levels of reliability performance. The prevention of such catastrophic incidents poses huge challenges for reliability study and operational practices in Buffalo City's sub-transmission network. Primarily investigations on the field shows, aging infrastructure, relay failures and reactive maintenance practice is eminent. Inspired by these challenges, this dissertation proposes an analysis of the critical transition in sub-transmission network from a lower level of reliability to an economically and acceptable level of reliability. The transition of the operational "stress" and its large scale of power interruptions are studied. The transition of the existing sub-transmission to the alternative sub-transmission models has been presented. The analysis of load flow and fault level calculations identifies the loading trends critical to cause operational "pressure" of unplanned interruptions. The results in this research work had to discover the most appropriate resolutions to aging equipment, reactive maintenance and protection systems. The DIgSILENT Power Factory simulates and quantifies the results of the problems that could occur in the sub-transmission network in the immediate future. Measures to mitigate any occurrence which might cause more prone to a catastrophic blackout are presented. The proposed corrective measures of upkeep aging infrastructure, relay responsiveness and planned preventative maintenance have been recommended. The development of these corrective measures and the proposed network model is the key to reaching higher levels of reliability performance in the energy supply that communities require in Buffalo City Metropolitan Municipality.